2016
DOI: 10.1111/ecin.12393
|View full text |Cite
|
Sign up to set email alerts
|

Party Affiliation and Public Spending: Evidence From U.S. Governors

Abstract: This paper investigates whether the party affiliation of governors (Democrat or Republican) has an impact on the allocation of state expenditures. Exploiting gubernatorial election results from 1960 to 2012 and a Regression Discontinuity Design (RDD), we find that Democratic governors allocate a larger share of their budget to health/hospitals and education sectors. We find no significant impact of the political party of governors on total spending, only on the allocation of funds. The results are robust to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…However, we also find that the exit rate of unincorporated self‐employed individuals is significantly lower under Republican governors. Consistent with recent findings (Beland and Unel ), the lower exit rate of unincorporated self‐employed individuals suggests that this group has better wage and salary job opportunities under Democratic governors. Our findings are robust to an extensive set of sensitivity analysis.…”
Section: Introductionsupporting
confidence: 88%
“…However, we also find that the exit rate of unincorporated self‐employed individuals is significantly lower under Republican governors. Consistent with recent findings (Beland and Unel ), the lower exit rate of unincorporated self‐employed individuals suggests that this group has better wage and salary job opportunities under Democratic governors. Our findings are robust to an extensive set of sensitivity analysis.…”
Section: Introductionsupporting
confidence: 88%
“…Therefore, the effects of government ideology on healthcare policies are a priori unclear. The empirical evidence as to whether government ideology predicts public health expenditure is mixed (Béland & Oloomi, 2017;Brändle & Colombier, 2016;Castro & Martins, 2018;Herwartz & Theilen, 2014;Jensen, 2011;Joshi, 2015;Kousser, 2002;Potrafke, 2010Potrafke, , 2012Wiese, 2014). Almost all previous studies use health expenditure as the dependent variable.…”
Section: Related Literaturementioning
confidence: 99%
“…This paper is related to a strand of the political economy literature that explores whether partisan allegiance of policymakers matters for policy outcomes. Several studies in this literature have analyzed the impact of party affiliation of governors on taxes, minimum wages, total spending, distribution of spending, pollution, family assistance, and worker compensation in the United States (Beland and Boucher ; Beland and Oloomi ; Besley and Case , ; Leigh ; Reed ; among many others). A growing number of studies in this literature have used RD designs to evaluate party effects in various contexts.…”
Section: Related Studiesmentioning
confidence: 99%
“…By having the right to veto state bills, governors have considerable control over state policies. Several studies have documented that the party allegiance of governors has a significant impact on their actions (Alt and Lowry ; Beland and Oloomi ; Besley and Case ; Knight , among many others). It has been shown that Democratic governors affect the labor markets of groups voting for them (target‐based policies): blacks (Beland ) and immigrants (Beland and Unel ).…”
Section: Introductionmentioning
confidence: 99%